Establishing the Effects of Growth Regulators on Melon Seeds and Plants - Dusmuratova Saodat Ismailovna; Akhmedova Munisa Abdimazhitovna (Web of Journals Publishing, 2023)
The article describes the effect of nanosilicon preparations and microparticles used in melons on the growth, development and productivity of plants.